Analisis Penerapan Marketing Mix dalam Pemasaran Tabungan Haji di BSI KCP AH Nasution - Aula Salsabila; Nurul Inayah; Kusmilawaty (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study analyzes the implementation of the marketing mix strategy (product, price, place, and promotion) in marketing Hajj Savings at Bank Syariah Indonesia (BSI) KCP AH Nasution and identifies the company’s strategic position using SWOT analysis. A qualitative descriptive approach was employed, with data obtained through observations, interviews, and documentation. The findings indicate that although all four elements of the marketing mix have been applied, their implementation has not yet been fully effective in meeting account-opening targets. Key product advantages—such as integration with the SISKOHAT system, funds guaranteed by BPKH, and digital access through BSI Mobile—have not been optimally communicated to prospective customers. Major challenges include perceptions of high costs, limited digital literacy, and promotional activities that are not sufficiently targeted. The SWOT analysis places BSI KCP AH Nasution in Quadrant I, indicating an aggressive strategic position in which internal strengths can be leveraged to capture external opportunities. Recommended strategies include strengthening educational promotions, expanding service outreach, enhancing digital features, building partnerships with religious institutions and communities, and developing loyalty programs for consistent savers.